2019
DOI: 10.1142/s0218625x19500677
|View full text |Cite
|
Sign up to set email alerts
|

MONITORED DEFORMATION BY POTENTIAL-INDUCED DEFECTS IN CH3(CH2)n−1SH SELF-ASSEMBLED MONOLAYERS ON GOLD: EIS STUDY OF CHAIN LENGTH EFFECT ON SUBDIFFUSION AND SAMs’ HETEROGENEITY

Abstract: From the defects-free self-assembled organic layers (SAMs) of CH3([Formula: see text]SH molecules with short chain lengths ([Formula: see text]) electrodeposited on the (111) surface of monocrystalline gold previously prepared, monitored defects (pinholes) were potential-induced from cyclic partial reduction of SAMs at an appropriate potential. Electrochemical impedance measurements were in-situ conducted and [Fe(CN)6][Formula: see text] ions were used as probes for mass and charge transfer. Interface evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The increase in oxygen reduction currents could be due to monolayer reorganization, which can drive the formation of defects or pinholes. 27 , 28 Interrogating the sensors at a 10-fold faster voltage scanning rate (1 V/s) showed less than 15% change in oxygen reduction currents, regardless of the DNA packing density ( Figure S1 ), and again no change in capacitive currents, confirming that blocking monolayer elements are almost fully retained after 14 days even under vigorous stirring at 25° C. Comparing the capacitive currents at t = 0 and t = 14 days relative to those measured on a bare gold electrode ( Figure 2 D), we confirmed that blocking monolayer elements remain on the electrode surface and that the observed increases in oxygen reduction currents are negligible relative to the faradaic currents observed on unfunctionalized electrodes. Finally, interrogating the sensors via square wave voltammetry resulted in voltammograms with identical peak currents when the sensors were functionalized with DNA packing density <1 pmol/cm 2 ( Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in oxygen reduction currents could be due to monolayer reorganization, which can drive the formation of defects or pinholes. 27 , 28 Interrogating the sensors at a 10-fold faster voltage scanning rate (1 V/s) showed less than 15% change in oxygen reduction currents, regardless of the DNA packing density ( Figure S1 ), and again no change in capacitive currents, confirming that blocking monolayer elements are almost fully retained after 14 days even under vigorous stirring at 25° C. Comparing the capacitive currents at t = 0 and t = 14 days relative to those measured on a bare gold electrode ( Figure 2 D), we confirmed that blocking monolayer elements remain on the electrode surface and that the observed increases in oxygen reduction currents are negligible relative to the faradaic currents observed on unfunctionalized electrodes. Finally, interrogating the sensors via square wave voltammetry resulted in voltammograms with identical peak currents when the sensors were functionalized with DNA packing density <1 pmol/cm 2 ( Figure S2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The last two points of the Nyquist representation go slightly out of the fit curve obtained with Zsim software. As these points are generally attributed to the phenomena of diffusions through the SAMs, caused by the local imperfections of the SAMs and / or due the roughness of the substrate itself, [21]…”
Section: Resultsmentioning
confidence: 99%
“…Some of our recent works show the quantification of gold electrodes modified by different types of thiols. [19][20][21] Changes at the double layer of the electrode surface are detectable at low frequencies, [18,22] this requires large stabilization time of the harmonic cycles; hence the choice of the frequencies defining the experimental low frequencies range is crucial. The spontanious adsorption of self-assembled monolayer's (SAM's) of alkanethiolates on gold electrode has been the subject of numerous reports.…”
Section: Introductionmentioning
confidence: 99%